PENGARUH CAR, ROE, RASIO MARJIN PENDAPATAN BERSIH DAN RASIO KREDIT TERHADAP TOTAL DEPOSIT TERHADAP PERUBAHAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN SYARIAH DI BURSA EFEK INDONESIA (BEI) - Arie Noviana (LPPM STIE Muhammadiah Bandung, 2019)
Since the banking business in Indonesia has experienced a crisis as a result of the monetary crisis and economic crisis that has plagued since mid-1997, many banking cases have occurred. In discussing banking cases, knowledge, information and experience are needed to be able to trace what actually happened, what was the cause, and how to follow up on surprising findings so that banking analysts must be carefulThe research taken in this study is quantitative because the purpose of this research is to find out how much the degree of relationship between the Capital Adequacy Ratio, Return on Equity, Net profit margin, and Loan to Deposit Ratio to stock price changes in Islamic banking companies in the Indonesian stock exchange.This research is also verification because this research is asking the relationship between two or more things.In general, collecting Bank Bukopin Syariah's capital is greater than other banks while the Sharia Agroniaga Bank is the least in fulfilling capital obligations set by Bank Indonesia, the lowest rate of return invested by Bank Mutiara Syariah when compared to other Banks while Bumi Putra Syariah ICB Bank is a Bank with a higher rate of return than others and investors will choose Bumi Putra Syariah ICB Bank from Bank Mutiara to invest, Bank Bukopin Syariah's ability to generate net income is greater than the others while the Bank Mutiara is a Bank that generates a smaller net income than other Banks, if the Bank is liquidated, Bank OCBC NISP Syariah is the highest bank in paying funds if withdrawn by the customer while Bank Permata Syariah Bank has the lowest value in pay customer funds.Simultaneously Capital Adequacy Ratio, Return on Equity, Net Profit Margin, Loan to Deposit Ratio have a significant influence on the Stock Price, Partially Capital Adequacy Ratio, Return on Equity Net Profit Margin, Loan to Deposit Ratio has a significant influence on stock prices